Roles of microRNAs in Ovarian Cancer Tumorigenesis: Two Decades Later, What Have We Learned? - Alshamrani, Ali A. (Frontiers in Oncology, 2020)
Ovarian cancer is one of the top gynecological malignancies that cause deaths among females in the United States. At the molecular level, significant progress has been made in our understanding of ovarian cancer development and progression. MicroRNAs (miRNAs) are short, single-stranded, highly conserved non-coding RNA molecules (19-25 nucleotides) that negatively regulate target genes post-transcriptionally. Over the last two decades, mounting evidence has demonstrated the aberrant expression of miRNAs in different human malignancies, including ovarian carcinomas. Deregulated miRNAs can have profound impacts on various cancer hallmarks by repressing tumor suppressor genes. This review will discuss up-to-date knowledge of how the aberrant expression of miRNAs and their targeted genes drives ovarian cancer initiation, proliferation, survival, and resistance to chemotherapies. Understanding the mechanisms by which these miRNAs affect these hallmarks should allow the development of novel therapeutic strategies to treat these lethal malignancies.